2007
DOI: 10.1007/s00442-007-0927-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of prey from the decomposer system by generalist predators of grassland

Abstract: We investigated the linkage between the detrital subsystem and generalist predators of meadow ecosystems by manipulating prey availability in two different ways: we increased resource availability for the decomposer subsystem and thereby decomposer prey by adding mulch materials (detritus enhancement), and we added fruitflies (Drosophila melanogaster, Diptera; prey enhancement) to fenced plots. Both supplemented materials significantly differed in their (13)C/(12)C and (15)N/(14)N ratios from those of the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 45 publications
4
60
1
Order By: Relevance
“…That same analysis did not uncover effects of habitat structure on the density of herbivorous prey, but not all types of potential prey were incorporated into the analysis and, as aptly noted, there are cases where arthropod predators accumulate in response to high densities of detritivores (Chen and Wise 1999;McNabb et al 2001;Halaj and Wise 2002;Oelbermann et al 2008). Indeed, other studies have shown that enhancing the decomposer community plays a role in the establishment of robust populations of predators living up in the vegetation (Scheu 2001;Rypstra and Marshall 2005).…”
Section: Introductionmentioning
confidence: 96%
“…That same analysis did not uncover effects of habitat structure on the density of herbivorous prey, but not all types of potential prey were incorporated into the analysis and, as aptly noted, there are cases where arthropod predators accumulate in response to high densities of detritivores (Chen and Wise 1999;McNabb et al 2001;Halaj and Wise 2002;Oelbermann et al 2008). Indeed, other studies have shown that enhancing the decomposer community plays a role in the establishment of robust populations of predators living up in the vegetation (Scheu 2001;Rypstra and Marshall 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, the absence of numerical response to resource supplementation is not necessarily due to the absence of either trophic linkage or bottom-up control (Oelbermann et al, 2008). Indeed, any increase in microbial activity leads to the destruction of the litter habitat as detritus is converted into microbial biomass and CO 2 (Kaspari et al, 2008a;).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased cannibalism and intraguild predation could have contributed to the absence of an effect on total spiders. Oelbermann, Langel & Scheu (2008) directly manipulated energy input to a grassland detrital web in fenced 5-m 2 plots for five months. Many Collembola families responded positively as did total spider numbers, which were ca.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments in terrestrial ecosystems have been conducted in prairies and grasslands (Fountain et al, 2008; Hoekman et al, 2011; Oelbermann, Langel & Scheu, 2008; Patrick, Kershner & Fraser, 2012) and forests (Chen & Wise, 1999; David et al, 1991; Lessard et al, 2011; Maraun et al, 2001; Raub et al, 2014; Salamon et al, 2006; Scheu & Schaefer, 1998; Yang, 2006). Most experiments uncovered some evidence for bottom-up control, but the strength and pervasiveness across trophic levels of the responses varied substantially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation